REALISASI KEBIJAKAN PENCITRAAN DESTINASI DI MONUMEN PERJUANGAN RAKYAT BALI - Ayu Wanda Febrian; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Perjuangan Rakyat Bali Monument as one of the historical attractions in Bali managed directly by government. Department of culture formed Technical Service Unit to managed the monument. In current management process, Perjuangan Rakyat Bali Monument based on policies that refers to the vision and mission of the approach of the Provincial Government of Bali. Based on this research, there is a realization of Perjuangan Rakyat Bali Monument as a destination image. Through comparative with the Bali Provincial Government policy found 19 items of total 43 comparators unrealized. The unrealized policy influence on destination image, so it is necessary to provide evaluation and repair the image of the destination as expected. While that has been realized for the total 24 items of total 43 comparators. From the comparative that has realized a number of 24 items we can conclude that destination image Perjuangan Rakyat Bali Monument as brand image or the the image is returned to tourist perspective.